2022
DOI: 10.1186/s13049-022-01003-7
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for mass gatherings: rescue and emergency medical services’ workloads during mass gathering events

Abstract: Background Mass gathering (MG) events may cause delayed emergency responses via various mechanisms and strain the resources of local emergency services. Therefore, preparedness, including adequate pre-planning and sufficient resourcing during MG events, is vital. The aim of this retrospective register study was to investigate the impact of MG events on the workload of rescue and emergency medical service (EMS) personnel during events to enable more precise and sufficient deployment of these aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…2,[27][28][29] They also could lead to delayed emergency responses and strain the resources of local emergency services. 30 Hence, implementing preparedness measures and action plans as well as ensuring resource planning and staff preparedness for any unexpected events is imperative. Disaster medicine is a discipline that incorporates emergency medicine and disaster management.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…2,[27][28][29] They also could lead to delayed emergency responses and strain the resources of local emergency services. 30 Hence, implementing preparedness measures and action plans as well as ensuring resource planning and staff preparedness for any unexpected events is imperative. Disaster medicine is a discipline that incorporates emergency medicine and disaster management.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…If only the fitness value is used to screen individuals, automatically adjust the cross regional emergency material dispatching route, build an intelligent cross regional emergency material dispatching route network structure model 16 , and obtain the path selection rules of population diversity awareness as follows: where c represents the fitness value, u 0 represents the individual divergence, and H represents the pathway network structure, represents the diversification selection weights, represents the importance of transporting materials. In different regions of the solution space, analyze individual structural models and represent the clustering center of the intelligent CREMS route with a quaternion G 17 , denoted as . There are m intelligent CREMS route nodes, denoted as , , and the departure time of vehicles at each key point is denoted as , .…”
Section: A Grid Distribution Model and Feature Analysis For Materials...mentioning
confidence: 99%
“…This could be attributed to the substantial health risks and pressure that accompany such events with the potential for a surge in demand for healthcare services that might strain the functioning of the host country's health system (2). Additionally, previous research showed that such events increase the workload especially for emergency medical services (3)(4)(5)(6). It may also cause delayed emergency responses via various mechanisms and stretch the resources of the local emergency services beyond their capacity (7).…”
Section: Introductionmentioning
confidence: 99%